2022
DOI: 10.1097/sap.0000000000003084
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Postoperative Pain in Autologous Breast Reconstruction With the Omental Fat–Augmented Free Flap

Abstract: Introduction The omental fat–augmented free flap (O-FAFF) is a recently developed technique for autologous breast reconstruction. Our aim of the study is to evaluate the outcomes of our early case series. We assess the O-FAFF donor site morbidity in terms of postoperative pain, narcotic, and antiemetic use. Methods A retrospective analysis of patients undergoing O-FAFF from 2019 to 2021 was performed. Patients were evaluated for demographic data, operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…A follow-up study showed that this technique resulted in less postoperative pain and shorter hospital stay compared to abdominally base free flaps (Deptula et al, 2022). Consistent with prior reports, T A B L E 1 (Continued) none of the patients in our series have reported symptoms suggestive of abdominal adhesions after omentum harvest or have required reoperations or readmissions for incarcerated bowel.…”
Section: T a B L E 1 Patient Demographics And Surgical Detailssupporting
confidence: 88%
See 1 more Smart Citation
“…A follow-up study showed that this technique resulted in less postoperative pain and shorter hospital stay compared to abdominally base free flaps (Deptula et al, 2022). Consistent with prior reports, T A B L E 1 (Continued) none of the patients in our series have reported symptoms suggestive of abdominal adhesions after omentum harvest or have required reoperations or readmissions for incarcerated bowel.…”
Section: T a B L E 1 Patient Demographics And Surgical Detailssupporting
confidence: 88%
“…Nguyen et al describes the novel technique of the omental fat‐augmented free flap use as a free flap for autologous breast reconstruction in those patients lacking adequate abdominal adiposity as well as in those patients who desire minimizing donor site morbidity with the use of laparoscopically harvested free omentum, alloderm and grafted fat (Nguyen et al, 2022). A follow‐up study showed that this technique resulted in less post‐operative pain and shorter hospital stay compared to abdominally base free flaps (Deptula et al, 2022). Consistent with prior reports, none of the patients in our series have reported symptoms suggestive of abdominal adhesions after omentum harvest or have required reoperations or readmissions for incarcerated bowel.…”
Section: Discussionmentioning
confidence: 99%